2018
DOI: 10.1097/ta.0000000000001798
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prehospital transport time, injury severity, and blood transfusion on survival of US military casualties in Iraq

Abstract: Performance improvement and epidemiological, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 23 publications
4
67
2
3
Order By: Relevance
“…Consistent data support the benefit of prehospital transfusion . Delayed evacuation further reinforces the importance of blood products being available closer to the site of injury and during evacuation, which justifies the provision of French lyophilized plasma (FLYP) for ground Role 1 medical teams and the transfusion of plasma and RBC during MEDEVAC since 2016 …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Consistent data support the benefit of prehospital transfusion . Delayed evacuation further reinforces the importance of blood products being available closer to the site of injury and during evacuation, which justifies the provision of French lyophilized plasma (FLYP) for ground Role 1 medical teams and the transfusion of plasma and RBC during MEDEVAC since 2016 …”
Section: Discussionmentioning
confidence: 73%
“…Consistent data support the benefit of prehospital transfusion. 2,3,[25][26][27][28] Delayed evacuation further reinforces the importance of blood products being available closer to the site of injury and during evacuation, which justifies the provision of French lyophilized plasma (FLYP) for ground Role 1 medical teams and the transfusion of plasma and RBC during MEDE-VAC since 2016. 13,14 Vitalis et al 13 described that 25% of Alpha casualties received prehospital transfusion in a similar area of operations between April 2016 and April 2017.…”
Section: Optimization Of Prehospital Transfusion Strategiesmentioning
confidence: 96%
“…The time from injury to definitive control of hemorrhage can vary dramatically according to circumstances. Although differences in prehospital transport times has little effect on mortality in hemodynamically stable patients, both military and civilian analyses indicate prehospital transport times are associated with an increased risk of mortality in patients with signs of active bleeding [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recognizing that more rapid transport to surgical hospitals is not always possible, recent trauma system advances have also focused on bringing additional resuscitation capabilities (remote damage control resuscitation) to the seriously injured in the form of prehospital blood transfusion; advanced hemostatic interventions; and light, maneuverable surgical teams . Prehospital transfusion in particular has been associated with improved survival in combat casualties . Not all studies of prehospital transfusion have demonstrated a survival benefit.…”
mentioning
confidence: 99%
“…16,43 Prehospital transfusion in particular has been associated with improved survival in combat casualties. 44 Not all studies of prehospital transfusion have demonstrated a survival benefit. However, an analysis of the time to transfusion among evacuated US military combat causalities in Afghanistan demonstrated that blood product transfusion within 36 minutes of injury was associated with improved survival.…”
mentioning
confidence: 99%